Retrofitting of Initially Damaged Beam Column Joint Using CFRP Confined UHP-HFRC - Goyal, Lovish (My University, 2019)
The beam column joint (BCJ) are considered as a vulnerable joint in a framed structure when subjected to cyclic load. The framed structures designed using pre-seismic codal provisions follow the non-ductile approach and the joint was not capable enough to resist the post elastic rotation. The absence of ductility in pre seismic designed reinforced concrete framed structures leads to greater extent of damage in BCJ. With the advent of revised design and detailing codes and increase in the earthquake vulnerability level of many regions, the existing structures need strengthening to conform to the revised codal provision. Therefore, there is a need of retrofitting of BCJ which will significantly improve its performance. The various types of materials used to improve the performance of BCJ e.g. Carbon Fiber Reinforced Polymer, Glass Fiber Reinforced Polymer, steel plates etc. Also, the various techniques such as Jacketing and pre-stressed CFRP has been used to retrofit the BCJ. However, the demerits associates with each technique restrict the performance of retrofitted structure elements. The demerit of jacketing is the increase in size due to encasement consequently the free inside space is reduced. The deb-bonding of CFRP at higher stress resulted in a brittle failure of retrofitted structures/elements. Therefore, it becomes necessary to use such retrofitting technique that can overcome these problems. Therefore, in the present study CFRP and ultra-high performance hybrid fiber reinforced concrete (UHP-HFRC) were used as retrofitting material for initially damaged BCJ. The development of UHP-HFRC was done by using OPC 53, silica fume, metakoalin, nano silica and steel fibers. The design mix of M20 grade of control specimen was designed according to IS code 10262:2009. The damage index level was calculated with the Park and Ang model to kNow the complete, severe, moderate and slight damage of BCJ. CFRP has been used in the published research as a laminate sheet on the joint but in the present study it was proposed as a CFRP strip mesh form that could be sandwiched between two concrete layers. Retrofitted BCJ was tested under cyclic loading to check the load displacement hysteresis graph. The test results indicated that CFRP confined with UHP-HFRC improves the displacement ductility, stiffness, energy dissipation, moment rotation, joint principle tensile strength and failure pattern of retrofitted specimen as compared to control specimen. The damage index level of BCJ increases, i.e. slightly to completely then ductility, stiffness, energy dissipation, moment rotation, joint principle tensile strength decreases.
Keywords: UHP-HFRC; Carbon Fiber Reinforced Polymer (CFRP); Retrofitting; Beam Column Joint